2001
DOI: 10.1016/s0169-7722(01)00139-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of herbicides to groundwater in an unconfined chalk aquifer following normal soil applications

Abstract: The persistence and penetration of the herbicides isoproturon and chlorotoluron in an unconfined chalk aquifer has been monitored over a 4-year period through soil sampling, shallow coring and groundwater monitoring. Chlorotoluron was applied on plots as a marker compound, having never been used previously on that, or surrounding fields. The fieldsite had a 5 degree slope with soil depths of 0.5 to 1.5 m and a water table between 20 and 5 m from the soil surface. Where the water table was deepest (9-20 m below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 17 publications
1
65
2
Order By: Relevance
“…However, in a groundwater sample taken from depth no such association with colloids is observed. This is despite the previous observations of Johnson et al (2001) and Gooddy et al (2001) which strongly suggested that pesticide concentrations in the shallow groundwater were controlled, at least in part, by the association of pesticides with colloidal material. This infers that either our method was too insensitive analytically to detect pesticides bound to colloids in the groundwater, or that the pesticide present was in a free (i.e.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…However, in a groundwater sample taken from depth no such association with colloids is observed. This is despite the previous observations of Johnson et al (2001) and Gooddy et al (2001) which strongly suggested that pesticide concentrations in the shallow groundwater were controlled, at least in part, by the association of pesticides with colloidal material. This infers that either our method was too insensitive analytically to detect pesticides bound to colloids in the groundwater, or that the pesticide present was in a free (i.e.…”
Section: Discussioncontrasting
confidence: 74%
“…It would appears therefore that the previous observations of Gooddy et al (2001) and Johnson et al (2001) pertaining to the likelihood colloidal transport of pesticides were correct. The fact that they were found at the study site was a function of the shallow depth from which the samples were taken.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In the United States, a considerable body of work exists relating to the occurrence of both parent compound pesticides and their metabolites in aquifers (Thurman et al, 1992;Baker et al, 1993;Lawrence et al, 1993;Kolpin et al, 1996;Kolpin et al, 1998;Kolpin et al, 2000a;Kolpin et al, 2000b). In the UK the number of field studies has been limited (Clark et al, 1991;Gooddy et al, 2001;Johnson et al, 2001) with researchers often concentrating on laboratory studies of transport and degradation potential (Johnson et al, 1998;Besien et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%